STRUKTUR KOMUNITAS FITOPLANKTON DI SEKITAR BENDUNG GERAK SERAYU BANYUMAS - musyarif zaenuri (Bioscientiae, 2026)
Serayu Movable Dam (BGS) is a water structure construction that crosses the Serayu River which aims to raise the water level so that it can be used to irrigate agriculture. Changes in air mass will form a community of air organisms. Phytoplankton are air organisms that develop following existing water conditions. The purpose of this study was to examine the diversity of phytoplankton in the waters of the Serayu Movable Dam. This research method uses surveys and stratified random sampling techniques, namely two locations before and two locations after the BGS gate. The main variables observed: Type and number of Phytoplankton. Supporting variables observed include: air and air temperature, Light Penetration, pH, Nitrate and Phosphate. The abundance of phytoplankton in the Serayu Movable Dam is relatively low and falls into the category of mesotrophic waters (moderate fertility). The phytoplankton found came from three main groups: Bacillariophyta, Chlorophyta, and Cyanophyta. Changes in air flow due to blockage affect the number and type of phytoplankton in each location. Air quality is generally still good and below the standard quality limit, but still needs to be maintained through routine management and monitoring.